Developing the Islamic scale of wisdom – general version (ISW-GV) - Rusdi, Ahmad; Nurtjahjo, Fani Eka; Afsari, Nyda; Sari, Ira Mayang; Puteri, Resha Karina; Nuraini, Anis Syifa; Amirza, Audi Vidya Putri (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The lack of a culturally grounded instrument to assess wisdom (ḥikmah) in general Muslim populations necessitates the development of a contextually relevant scale. This study introduces the Islamic Scale of Wisdom – General Version (ISW-GV), constructed from Ibn Miskawaih’s conceptualization of ḥikmah as a balanced cognitive-reflective virtue, addressing the limitations of Western-based wisdom measurements that tend to emphasize cognitive and experiential aspects while overlooking the moral and virtuous dimensions central to Islamic thought. Research was conducted across 857 respondents through Exploratory and Confirmatory Factor Analysis, and correlational tests. Results supported a stable four-factor structure (problem solving, learning, reflecting, and understanding) with satisfactory model fit indices. Convergent evidence was confirmed through positive correlations with HS, ISW-AV, and 3D-WS, while discriminant evidence was demonstrated via weak associations with GPA and social desirability. Criterion-related analysis showed that wisdom correlated positively with subjective happiness among adult workers but not among students, suggesting developmental variation in the function of ḥikmah. These outcomes support ISW-GV as a valid and context-sensitive instrument for capturing wisdom across everyday settings. However, response patterns indicate that the current bipolar item format (1-2-3-2-1) may blur distinctions between ḥikmah, rashness, and stupidity. Future refinements using rank-order Situational Judgment Test formats may enhance its assesment precision in mapping ethical reasoning across value orientations.